Teaching of English as a performing art: reflecting on its role in the curriculum - Abdullah, Nur Surayyah Madhubala (Universiti Putra Malaysia Press, 2012)
This paper is a reflection on how conceptualising the teaching of English as a performing art within the English Language school curriculum in Malaysia can play a meaningful and practical role in developing an adequate moral stance of students towards other members of its plural society. It is argued that, in addition to being an interesting and creative way of teaching language, the different forms of performing art also present a realistic experience of others. It offers an opportunity for pupils through the use of aesthetics to better inform pupils’ perception of others centred in a realism brought to life by the arts. This argument is considered within the context of Malaysia, as a plural society and the roles of the teaching and learning of language in developing a much more adequate moral sensibility about others through imagination and perception. The argument draws on Murdoch’ ideas about the relationship between ethics and art and the authentic representation of the reality of life in plural society it offers. Based on the argument forwarded, it is suggested that a conceptualisation of English Language Teaching as a performing art can play a deeply meaningful role in developing the moral sensibilities of pupils towards other members of the society in raising their awareness and understanding about others as people. The paper concludes by recommending that this idea of the teaching of English is adopted depending on the aim of the curriculum.